MECHANISMS FOR ENSURING ENVIRONMENTAL SAFETY THROUGH DIGITAL TECHNOLOGIES IN PLANT MONITORING - Ruzimova Xolida Kamiljanovna (Modern American Journals, 2025)
The study examines the mechanisms of ensuring environmental safety in plant monitoring through the application of digital technologies. In recent years, the integration of digital systems into environmental and biological research has enabled a new level of precision in observing plant conditions, ecosystem dynamics, and environmental impacts. The digitalization of plant monitoring encompasses technologies such as remote sensing, geographic information systems (GIS), Internet of Things (IoT), artificial intelligence, and data analytics, which together facilitate real-time monitoring and predictive analysis. This research highlights how these technologies contribute to identifying ecological risks, optimizing resource use, and preventing environmental degradation. The study also focuses on the development of algorithmic systems for early warning of ecological hazards and the automation of data processing for sustainable decision-making. The integration of digital monitoring tools into environmental management provides a foundation for sustainable agriculture, biodiversity protection, and the rational use of natural resources. The paper further discusses the need for interdisciplinary collaboration between biologists, ecologists, and data scientists to ensure the effective implementation of these systems. The results indicate that digital plant monitoring not only enhances ecological safety but also supports the formation of a data-driven environmental management culture.
Keywords: Digital monitoring, environmental safety, plant ecosystems, GIS, IoT, artificial intelligence, data analytics, sustainability, early warning systems, biodiversity.